PELATIHAN ADMINISTRASI PERKANTORAN BAGI PENGURUS AHLI SUNNAH WALJAMAAH KOTA MALANG - Mohammad Maskan; Lilies Nur Ainie; Nilawati Fiernaningsih; Pudji Herijanto; Rulirianto Rulirianto; Oto Sunandar Dinata (Publisher UPT P2M Politeknik Negeri Malang, 2017)
A successful organization is an organization that can effectively manage its administration, both internally and externally. This is understandable, because the administration is the process of managing information among members of the organization and with other parties related to the interests of the organization. The better the administration takes place the better the organization's operations are concerned. For that, it takes the ability of the administration to manage resources within the organization for the achievement of these goals. Related to that, it is necessary training office administration. The purpose of this training is to provide knowledge to the managers of the Ahlussunnah Waljamaah Foundation Malang about effective office administration, both verbal communication and non verbal communication (correspondence) so that they know and are able to manage the administration properly The training method used is with lectures, and administrative practices. While the analytical techniques used are from cognitive, affective and psychomotor aspects during the training and after the training.